2019
DOI: 10.1111/vsu.13164
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic variables associated with central division hepatic lobectomies: 61 dogs

Abstract: Objective: To determine the outcome and prognostic variables associated with long-term survival and complications in dogs undergoing hepatic lobectomy of the central division. Study design: Multi-institutional retrospective case series. Animals: Sixty-one client-owned dogs with central division masses. Methods: Medical records of dogs undergoing hepatic lobectomy of the central division from January 1, 2000 to January 1, 2015 were reviewed for signalment, clinical signs, preoperative staging, preoperative cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 11 publications
7
50
0
Order By: Relevance
“…However, two dogs exsanguinated intraoperatively as a result of trauma to the caudal vena cava during attempted resection of a right‐sided liver tumor. In the study by Linden et al, partial and total lobectomies were successfully performed with a TA stapler (42), a vascular sealing device (6), hilar resection (6), or a circumferential ligature (4). Those two studies reported rates of 23.8% for hemorrhage during single hepatectomies and 31.1% for blood transfusions during central division lobectomies .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, two dogs exsanguinated intraoperatively as a result of trauma to the caudal vena cava during attempted resection of a right‐sided liver tumor. In the study by Linden et al, partial and total lobectomies were successfully performed with a TA stapler (42), a vascular sealing device (6), hilar resection (6), or a circumferential ligature (4). Those two studies reported rates of 23.8% for hemorrhage during single hepatectomies and 31.1% for blood transfusions during central division lobectomies .…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Linden et al, partial and total lobectomies were successfully performed with a TA stapler (42), a vascular sealing device (6), hilar resection (6), or a circumferential ligature (4). Those two studies reported rates of 23.8% for hemorrhage during single hepatectomies and 31.1% for blood transfusions during central division lobectomies . The variety in instrumentation and blood loss highlights the particular technicality and complexity of partial and complete liver lobectomies and supports the requirement to identify safer surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations